CREATIVITY AND INNOVATIVE BEHAVIOR TO ENHANCE COMPETITIVE ADVANTAGE WITH THE MODERATING ROLE OF DIGITAL LEADERSHIP - Susanto, Yohanes; Lian, Bukman; Marisya, Fitria (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The purpose of this study is to better understand the value of creativity and creative work practices in boosting competitive advantage, starting with psychological empowerment via the mediating impact of digital leadership. In this study's quantitative methodology, 300 SMEs in Palembang City, South Sumatra, Indonesia, were given questionnaires to complete. Path analysis using SEM-PLS is the analysis method employed. The study's findings indicate that psychological empowerment directly influences creativity and innovative work behavior but has no impact on competitive advantage. While creativity promotes new work practices, competitive advantage is unaffected. Competitive advantage is impacted by innovative work practices. Innovative work practices and competitive advantage are mediated by creativity, although competitive advantage is not one of them. Digital leadership does not mediate psychological empowerment and creativity into a competitive advantage, but it does mediate creativity into innovative work behavior and innovative work behavior into a competitive advantage. As a result, it will be simple to mold employees' innovative behavior. Creativity is required to compete in the modern world, and it must be based on the desires of the employees themselves. This creative conduct will encourage the growth of small and medium-sized businesses. Leaders must keep up with trends and technical advancements and be able to help staff members advance their IT literacy. As a result, it will quicken behavioral adjustments necessary to be creative and successful in the contemporary technological era.